Aproximación a un Estudio Estilístico de la Fraseología Representada en la Crónica Troyana (Juan de Burgos, 1490) - Vicente Llavata, Santiago (2021)
This article aims to contribute to the knowledge of Medieval Hispanic Phraseology by means of the stylistic analysis of the phraseological units, which are represented in the Crónica troyana (Juan de Burgos, 1490). To achieve this aim, this study is based on the methodological program proposed by Echenique Elizondo (2003), in order to tackle the historical and stylistic analysis of these units. From the selection of two passages referring to amor and to militia in the context of the Matter of Troy, the combinations contained in the Crónica troyana will be analyzed in contrast to the rest of peninsular versions derived from the Historia destructionis Troiae (c. 1287). This is intended to advance the knowledge of the phraseology represented in the narrative tradition of the Matter of Troy in the Hispanic domain.
Keywords: Burgos, Juan de, -- fl. 1489-1502; Estilística; Fraseología